Consulting report - CAC Oro Verde - Pérez Cosavalente, Carlos Enrique (2017)
CAC Oro Verde is a Peruvian coffee and cocoa cooperative located in San Martín, Peru which is seeking to explore a niche market of cocoa beans located in Canada. Thus, the main objective of this consulting report is to identify and develop a plausible business opportunity within this market. For that purpose, a marketing strategy, a marketing mix and a financial assessment were developed in order to have a clear implementation plan for this business opportunity. Based on the analysis, the main opportunity identified is the fine flavour Fair Trade and Organic certified cocoa beans market. Moreover, considering the possibilities of the cooperative and the segments that were analyzed, the bean-to-bar segment was identified as the target market. Moreover, direct exporting and developing a partnership are the two most suitable entry methods for the bean-to-bar segment and British Columbia was identified as the best location to penetrate. The marketing mix suggested was deployed in an implementation plan with a timeline of 30 weeks and a cost estimated in 109,000 USD. Due to the fact that the recommended product to enter the market is considered a premium and high-quality product and, considering other benchmarks of the market, then the prices proposed are from 5,000 USD to 6,500 USD. Furthermore, the project was financially assessed considering 18 different scenarios varying prices and percentages of market share. From that, it was determined that the breakeven points in terms of market share are from approximately 4.9% for the 6,500 USD price to 6.1% for the 5,000 USD price. These percentages of market shares represent between 8.9 TNE to 11 TNE per year in order to break even in such a niche market. For the best-case scenario, CAC Oro Verde has the potential to make a net profit of approximately 530,000 PEN in year one if the cooperative is able to attain 20% market share which in five years would represent a net present value of approximately 3’400,000 PEN which indicates a 192.4% internal rate of return on the initial investment showing that the project is feasible and viable